Design, synthesis, and evaluation of carboxyl-modified oseltamivir derivatives with improved lipophilicity as neuraminidase inhibitors. Issue 21 (15th November 2018) - Wang, Boyu; Wang, Kuanglei; Meng, Peipei; Hu, Yaping; Yang, Fei; Liu, Kemin; Lei, Zaiqiang; Chen, Binfeng; Tian, Yongshou
Graphical abstract: Highlights: A series of carboxyl-modified oseltamivir analogs with improved lipophilicity were designed and synthesized. Inhibitory activities of compounds against neuraminidase from influenza A virus H5N1 subtype were evaluated. The molecular docking studies of5m was performed. Compound5m targeted the recently discovered 430-cavity. Lipophilicity and metabolic stability of compound5m were evaluated. Abstract: In this study, a series of carboxyl-modified oseltamivir analogs with improved lipophilicity were designed and synthesized, and their inhibitory activities against neuraminidase from influenza A virus H5N1 subtype were evaluated. The results demonstrated that compound5m exhibited potent inhibitory activity (IC50  = 1.30 ± 0.23 μM), and it targeted the recently discovered 430-cavity. Compound5m (Log D = −0.12) is more lipophilic than oseltamivir carboxylate (Log D = −1.69) at pH 7.4, which is potentially propitious to improved membrane permeability and oral drug absorption. Meanwhile, 5m showed high stability in human liver microsomes. The findings of this study can be valuable in identifying neuraminidase inhibitors with optimal lipophilicity and in the exploration of 430-cavity.